El ritual de culpa en las historias Raymond Chandler - BURILLO GADEA, M. Rosa (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2010)
The popular novel is a real literary catechism for the reader, which all the implications about, belief and faith in the good. The narrative strategy of these stories is based upon the Western ritual of guilt detection, the necessary sacrifice of an innocent, the taking of conscience and the restoration of order. This paper aims to show how the same structural procedure happens in crime fiction, where the evil stays in the bureaucratic and consumer North-American society. We will try to prove our line using quotations from Raymond Chandler’s “Pearls are a Nuisance” and